TRADISI POTANG BALIMAU DI NAGARI PANGKALAN KECAMATAN PANGKALAN KOTO BARU KABUPATEN LIMA PULUH KOTO - Ananda, Dhea Putri; Sidiq, Siti Sofro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research aims to study the Potang Balimau tradition in Nagari Pangkalan, Pangkalan Koto Baru Subdistrict, Lima Puluh Kota Regency, held as a preparation for the holy month of Ramadan. Potang Balimau involves a cleansing ritual using lime juice and a mixture of seven types of flowers, along with a series of cultural activities such as traditional competitions and performances. This research employs a descriptive qualitative approach with data collection methods including interviews, observations, and documentation. The findings reveal that the Potang Balimau tradition holds deep spiritual and social significance for the local community. Beyond purification, it strengthens social bonds and preserves the cultural values of the Minangkabau people. Keywords: Potang Balimau Tradition, Social Values, Purification